2011
DOI: 10.1093/ntr/ntq257
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Services in a Randomized Trial Testing Phone- and Web-Based Interventions for Smoking Cessation

Abstract: Introduction: Phone counseling has become standard for behavioral smoking cessation treatment. Newer options include Web and integrated phone-Web treatment. No prior research, to our knowledge, has systematically compared the effectiveness of these three treatment modalities in a randomized trial. Understanding how utilization varies by mode, the impact of utilization on outcomes, and predictors of utilization across each mode could lead to improved treatments. Methods:One thousand two hundred and two particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 34 publications
(50 reference statements)
6
31
0
1
Order By: Relevance
“…Inconsistent with the results of Balmford, Borland, Benda, and Howard (2013) and Zbikowski et al (2011) – this website engagement did not differ in the two Web interventions (Web + Quitline= 90.4%; Web Only= 90.0%;). It is important to note further that the level of Web visits we observed was higher than in our previous Web-based smokeless tobacco cessation RCTs (Danaher et al, 2013; Danaher et al, 2015; Severson et al, 2008) as well as reported by Cobb and Graham (2014) for smokers who called a commercial Quitline (QuitNet.com) 25% of whom never logged into their assigned Web intervention.…”
Section: Discussionsupporting
confidence: 76%
“…Inconsistent with the results of Balmford, Borland, Benda, and Howard (2013) and Zbikowski et al (2011) – this website engagement did not differ in the two Web interventions (Web + Quitline= 90.4%; Web Only= 90.0%;). It is important to note further that the level of Web visits we observed was higher than in our previous Web-based smokeless tobacco cessation RCTs (Danaher et al, 2013; Danaher et al, 2015; Severson et al, 2008) as well as reported by Cobb and Graham (2014) for smokers who called a commercial Quitline (QuitNet.com) 25% of whom never logged into their assigned Web intervention.…”
Section: Discussionsupporting
confidence: 76%
“…Smokers that participate in web-based cessation studies are often highly motivated to quit smoking (Graham et al, 2011;Richardson et al, 2013;Saul et al, 2007;Zbikowski et al, 2011) and may seek out additional "non-assigned" cessation methods beyond the interventions assigned in the trial. Not unlike participants in other types of studies, those who join Internet cessation trials are free to avail themselves of other cessation interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Motivation to participate in face to face smoking reduction and cessation programs is typically high. Yet, it was shown that online users that are effectively engaged are as successful as those participating in more difficult to access and more expensive face to face programs (Christensen et al, 2004;Eysenbach, 2005;Farvolden et al, 2005;Zbikowski et al, 2011). But face to face programs are not as readily available worldwide as internet based interventions.…”
Section: Introductionmentioning
confidence: 99%